Retrospective observational analysis of ferric pyrophosphate citrate (triferic®) administered via dialysate. Experience at a single facility over 2 years - Marc Hoffman; Richard Delvalle; Raymond D Pratt (Archives of Clinical Nephrology - Peertechz Publications, 2021)
Background: Ferric pyrophosphate citrate (FPC, Triferic®) is a unique form of iron therapy that is indicated to maintain iron balance and hemoglobin concentration in adult hemodialysis patients. We conducted an analysis of observational data from an independent dialysis facility that has administered FPC via the central delivery system to all patients in the facility over a 2‑year period to determine if FPC would offer pharmacoeconomic benefits over the current anemia management protocol that was used at the dialysis facility. Methods: FPC was administered in the dialysate to 61 patients via the central delivery system from first quarter 2017 through fourth quarter 2018.Anonymized data were obtained from the Electronic Medical Record of the dialysis facility. Data were summarized descriptively. The analysis used the last quarter (3 months) of data before initiation of FPC as baseline values. Data were aggregated by quarter and presented as total administered dose, average dose per patient or as average per patient‑year exposure.  Results: FPC reduced the need for supplemental intravenous iron use by an average of 74% over the 2-year observation period and reduced the amount of erythropoietin‑stimulating agents needed to maintain hemoglobin levels within the target range of 10.0 to 11.0 g/dL. Small mean improvements in quality of life were observed, as assessed by the 36-item Kidney Disease Quality of Life Questionnaire (KDQoL-36™) mental and physical component scores. As compared with US Renal Data System (USRDS) data, all-cause hospitalizations, infection‑related hospitalizations, and deaths were reduced by approximately 50% after initiation of FPC. Conclusions: Implementation of FPC as an iron maintenance therapy for all patients in a chronic hemodialysis center may result in improvements in anemia management and patient outcomes and in pharmacoeconomic benefits to the dialysis center.